Use of Biographical Recount of Famous Scientists to Enhance Scientific Literacy for New Pre-Service Primary Science Teachers at the Lebanese University - Hanadi Chatila (Journal of Education in Science, Environment and Health)
The preparation of scientifically literate citizens able to use science in their daily life is becoming a major goal in science education. In light of this, Boujaoude (2002) developed a framework to investigate the balance of scientific literacy themes within the Lebanese school science curriculum.   He reported the neglect of “science as a way of knowing” in the Lebanese science curriculum and national textbooks. The purpose was determining the perception of pre-service primary science teachers, at the Lebanese University- Faculty of Education, of science and scientists, and examining their scientific literacy according to BouJauode (2002) framework. In addition, the study investigated whether the use of biographical recounts of famous scientists would enhance scientific literacy, and promote science as “a way of knowing” in classrooms. It was found that participants perceived science mainly as a body of knowledge, and that the implementation of the biographical recount activity exposed them to other aspects of science, and helped them enhance their scientific literacy.